A CROSS-SECTIONAL STUDY: THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND MENTAL WORKLOAD AMONG HOUSEWIVES: Hubungan Aktivitas Fisik dengan Beban Kerja Mental pada Ibu Rumah Tangga - Wahyu Ismiyasa, Suci; Mailani, Rena (Jurnal Berkala Epidemiologi, 2025)
Background: The role of housewives, particularly those with toddlers, is physically and mentally demanding, often leading to high stress levels and workload. Purpose: This study examined the relationship between physical activity and mental workload among homemakers. Methods: A cross-sectional design was employed, utilizing the IPAQ-SF and RSME questionnaires to assess physical activity and mental workload. The study included 46 participants, most of whom were young mothers with one child and had a high school education. Results: The mothers had a high level of physical activity (16,479.85 ± 16,983.35 MET-min/week) and experienced a considerably quite large workload (mean score: 72.90). However, there was no significant relationship between physical activity and mental workload (β = 0.28, p > 0.05). Conclusion: These findings suggest that the physical and mental demands on homemakers are substantial, yet these factors may not directly influence their life satisfaction, highlighting the need for further research into the contributors to their well-being.